Cloning and characterization of herpes simplex virus type 1 oriL: comparison of replication and protein-DNA complex formation by oriL and oriS. - Hardwicke, M A (1995)
The herpes simplex virus type 1 genome contains three origins of DNA replication: two copies of oriS and one copy of oriL. Although oriS has been characterized extensively, characterization of oriL has been severely limited by the inability to amplify oriL sequences in an undeleted form in Escherichia coli. We report the successful cloning of intact oriL sequences in an E. coli strain, SURE, which contains mutations in a series of genes involved in independent DNA repair pathways shown to be important in the rearrangement and deletion of DNA containing irregular structures such as palindromes. The oriL-containing clones propagated in SURE cells contained no deletions, as determined by Southern blot hybridization and DNA sequence analysis, and were replication competent in transient DNA replication assays. Deletion of 400 bp of flanking sequences decreased the replication efficiency of oriL twofold in transient assays, demonstrating a role for flanking sequences in enhancing replication efficiency. Comparison of the replication efficiencies of an 822-bp oriS-containing plasmid and an 833-bp oriL-containing plasmid demonstrated that the kinetics of replication of the two plasmids were similar but that the oriL-containing plasmid replicated 60 to 70% as efficiently as the oriS-containing plasmid at both early and late times after infection with herpes simplex virus type 1. The virus-specified origin-binding protein (OBP) and a cellular factor(s) (OF-1) have been shown in gel mobility shift experiments to bind specific sequences in oriS (C.E. Dabrowski, P. Carmillo, and P.A. Schaffer, Mol. Cell. Biol. 14:2545-2555, 1994; C.E. Dabrowski and P.A. Schaffer, J. Virol. 65:3140-3150, 1991). Although the nucleotides required for the binding of OBP to OBP binding site I in oriL and oriS are the same, a single nucleotide difference distinguishes OBP binding site III in the two origins. The nucleotides adjacent to oriS sites I and III have been shown to be important for the binding of OF-1 to oriS site I. Several nucleotide differences exist in these sequences in oriL and oriS. Despite these minor nucleotide differences, the protein-DNA complexes that formed with oriL and oriS sites I and III were indistinguishable when extracts of infected and uninfected cells were used as the source of protein. Furthermore, the results of competition analysis suggest that the proteins involved in protein-DNA complex formation with sites I and III of the two origins are likely the same.